Bridging Language Gaps: A Dive Into Cross-Lingual Named Entity Transliteration in Chinese - Nayak, Somya; Mukhopadhyay, Biatrisha (Journal of Maobi, 2024)
Language is a fundamental component of culture and identity. The transliteration of language names into Chinese, a complex task requiring a deep understanding of both linguistic and cultural nuances, has been the subject of ongoing research and debate. This article delves into a comprehensive project conducted to explore the transliteration of various language names into Chinese. It discusses the methods employed, the challenges faced, and the implications of these transliterations on cross-cultural communication and understanding. The project deals with the transliteration of Proper Nouns such as names of person and place in Mandarin.  The proper nouns pertaining to names of people from different language family including Indian names, Arabic names as well western names into Mandarin. Named entity the project aims to develop a comprehensive transliteration system for the names of places located in the border areas into Mandarin. Transliterating border area place names into Mandarin, this project seeks to enhance cross-border interactions. Some of the primary tasks are to compile a database of place names in the border areas of the country. Moreover, to develop a transliteration system that accurately represents the phonetics and pronunciation of the place names into Mandarin. To develop a transliteration system that adheres to Mandarin pronunciation rules and captures the phonetic nuances of the place names. The process involves engaging linguists and experts in the development and validation of the transliteration system and phonetic sound recordings of the transliterated contents. A guidebook for reference and usage has also been part of the project. The outcomes of this project will benefit various stakeholders, including government agencies by providing an accurate representation of the border area place names and names of person (Named Entities) in Mandarin.